Disorders of carbohydrate metabolism in Carbon nephropathy - Garmendia, Fausto (1969)
174 people studied , 91 were normal controls, 55 nephropathy with renal insufficiency ( CIR ) and 28 without renal failure ( SIR) . The standard test of glucose tolerance (TST ) in 102 , being a definite intolerance in nephropathy , which was greater in the CIR group was performed . The differences between the 3 groups were statistically significant from 90 minutes. The tolbutamide test ( TT ) conducted in 83 subjects showed a decrease with poor resilience in response nephropathy . The curves allow differentiation found curves diabetics. Tolbutamide index also allowed differentiation between the 3 groups . The glucagon test (TG ) conducted in 20 subjects suggests the existence of a normal glycogenolysis in nephropathy , which showed a hyperglycemic response than controls. Relationship between the magnitude of serum creatinine of nephropathy with the degree of abnormality of test glucose tolerance , expressed in terms of glycemia of 2 hrs was observed . , Not the test of tolbutamide or the test of glucagon. Mechanisms are likely to explain the changes found are discussed , which favor the idea that there is less use of glucose to peripheral cellular level , highlighting the importance of intracellular electrolyte disturbances as the most intriguing mechanism.